Síndrome de burnout em dentistas do serviço público - Bonafé, Fernanda Salloume Sampaio; Trotta, Odete Sinhoreli Thereziano; Campos, Juliana Alvares Duarte Bonini [UNESP]; Maroco, João (Leibniz Institute for Psychology (ZPID), 2012)
Objective: to assesses the prevalence of the Burnout Syndrome in surgeon-dentists, from the public health service, and its association with variables of interest. Method: The study included a total of 60 professionals from the public health service in the city of Araraquara – SP, Brazil. A socio-demographic and labour questionnaire and the Maslach Burnout Inventory (MBI) were used. Descriptive statistics and an association study, using the chi-square test, were applied. Results: A total of 60.0% of the participants were women and the mean age was of 41.9±7.6 years. Most professionals had a regular perception of their working conditions, facilities, materials and equipment. 20.0% of the individuals felt emotionally drained by work, 35.6% worn out at the end of a workday, 27.1% when waking up to face another day at work, and 17.2% often feel consumed by work. The prevalence of Burnout was of 16.7%. There was a significant association between high Burnout levels and the time working in public service (p=0.017), being the professionals with less than 10 years of experience the most affected ones. Conclusion: The onset of Burnout Syndrome in civil servants highlights the need for developing coping strategies especially aimed at professionals with less seniority.

Objetivo: verificar a prevalência da Síndrome de Burnout em cirurgiões-dentistas do serviço público e sua associação com as variáveis de interesse. Método: Participaram do estudo 60 profissionais da rede pública de Araraquara-SP. Foram utilizados um questionário com informações sociodemográficas e laborais e o Inventário de Burnout de Maslach (MBI). Realizouse estatística descritiva e estudo de associação por meio do teste de qui-quadrado. Resultados: Dos participantes 60,0% eram mulheres e a média de idade foi de 41,9±7,6 anos. Grande parte dos profissionais apresentou perceção regular das condições de trabalho, instalações, materiais e equipamentos. Dos indivíduos, 20,0% sentem-se emocionalmente esgotados pelo trabalho, 35,6% esgotados no final de um dia, 27,1% quando se levantam para enfrentar outro e 17,2% sentem-se consumidos pelo trabalho frequentemente. A prevalência de Burnout foi de 16,7%. Verificou-se associação significativa entre Burnout elevado e o tempo de atividade no serviço público (p=0,017) sendo mais atingidos os profissionais com menos de 10 anos de atuação. Conclusão: O acometimento de servidores públicos pela Síndrome de Burnout sinaliza para a necessidade de elaboração de estratégias de enfrentamento principalmente voltadas para os profissionais com menor tempo de serviço.
Burnout syndrome in public service dentists
Keywords: Occupational health; Professional burnout; Dentistry; Public health; Saúde do trabalhador; Esgotamento profissional; Odontologia; Saúde pública